2006
DOI: 10.5688/aj700474
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students' Learning Styles Before and After a Problem-based Learning Experience

Abstract: Objectives. To determine learning-style scores of second-year pharmacy students before and after a problem-based learning (PBL) teaching experience and to evaluate the relationships between scores and demographic variables. Methods. The Grasha-Reichmann Student Learning Style Scale (GRSLSS) was given to pharmacotherapy laboratory students before and after a semester-long problem-based learning class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 14 publications
(13 reference statements)
3
31
2
5
Order By: Relevance
“…In one study involving problem-based learning, students' learning style preferences changed during the course of a single semester. 11 While each style may suggest a certain preference for a specific learning strategy, a learning style is not all encompassing. For example, people may prefer to learn by action, but that does not mean they cannot also learn by reading.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study involving problem-based learning, students' learning style preferences changed during the course of a single semester. 11 While each style may suggest a certain preference for a specific learning strategy, a learning style is not all encompassing. For example, people may prefer to learn by action, but that does not mean they cannot also learn by reading.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is evidence that simply knowing a student's learning style improves student learning, independent of the teaching method used. 11 Learning style inventories, like PILS, could be used by students and preceptors to initiate discussions about learning. It should not be used as a predictor of success, but rather to make each other aware of the ways they like to teach and learn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of pharmacy students' learning styles showed that increased use of the Avoidant learning style led to a decrease in using the Participant learning style in a problem-based learning curriculum. [20] However, these researchers do concede that this finding might have been due to the difficulties in adapting to changes in the learning method. The finding of Novak et al [20] partly concurs with the finding of this study where graduates scored low on cooperative learning efforts (2.49) and participation in small group learning (2.55) while simultaneously scoring high on avoidance variables.…”
Section: Discussionmentioning
confidence: 90%
“…Both tutors and learners will benefit from heuristic teaching. Knowledge is more accessible with more opportunity to form mental network and internal relations and can be easily transformed into innovative potential and action [3].…”
Section: Introductionmentioning
confidence: 99%